Buddhist feminism: transforming anger against patriarchy - Yeng, Sokthan (Palgrave studies in comparative East-West philosophy, 2020)
What is Buddhist Feminism? This book examines reasons why Buddhism and feminism may seem to be incompatible, and shows that Buddhist and feminist philosophies can work together to challenge patriarchal structures. Current scholarship usually compares Buddhism and feminism to judge their compatibility, rather than describing a Buddhist Feminist perspective or method. Sokthan Yeng instead looks for a pattern that connects Buddhist and feminist traditions. In particular, she explores possible exchanges between feminist and Buddhist philosophies which highlight how they each contribute to a more nuanced understanding of anger. Yeng explores how a Buddhist feminist approach would allow womens anger to be transformed from that which is outside the bounds of philosophy into that which contributes to philosophical discourse in the East and West, and between the two